Will the Euro Bring Economic Crisis to Europe? - Philip Arestis; Malcolm Sawyer (Levy Economics Institute of Bard College, 2001)
The initial introduction of the euro has, against many expectations, been accompanied by a decline in the value of the euro (notably vis-à-vis the dollar and sterling). It has also been introduced at a time of high levels of unemployment within most of the European Union (EU). This paper explores how the economies of the EU may suffer from the introduction of the euro, specifically from the policy and institutional arrangements within which the euro is embedded. It is the argument of this paper that the eurozone will face considerable economic difficulties. These difficulties will take a number of forms, but we focus on two rather different aspects which could qualify for the term crisis. First, the euro has been launched with high levels of unemployment (of the order of 10 percent of the work force) and with particularly severe disparities in unemployment experience and in standards of living. At the end of 1998, the rate of unemployment was over 20 percent in Spain, and in double figures in Finland, France, Germany, Ireland and Italy. It is argued here that these high levels of unemployment are likely to continue in the foreseeable future, and that the policy arrangements which surround the operation of the euro, notably the objectives of the European Central Bank (ECB) and the workings of the Stability and Growth Pact, will have a deflationary bias. These levels of and disparities in unemployment could be termed a crisis. Second, the introduction of the euro and the associated institutional setting could well serve to exacerbate tendencies towards financial crisis including the volatility and subsequent collapse of asset prices and runs on the banking system. There may be some additional forces of instability arising from the relationship between the dollar and the euro as two major global currencies and the current trade imbalances. Further, the operating arrangements of the European System of Central Banks (ESCB) can be seen as inadequate to cope with such financial crises.
Keywords: 330; Euro; Europäische Wirtschafts- und Währungsunion; Wirtschaftskrise; Finanzmarktkrise; EU-Staaten